Monitoramento e investigação ecoepidemiológica da contaminação por Staphylococcus spp. no beneficiamento do leite de cabra - Leon, Candice Maria Cardoso Gomes de (2014)
The present study had as objective to monitor the contamination buy Staphylococcus spp. in small-scale milk processing plants in Cariri of Paraiba through a quantitative microbiological analysis and by genotyping of the isolates by REP-PCR method (Repetitive Extragenic Palindromic Sequences). For both, considering the flow chart of processing of pasteurized goat milk in plants, sampling of raw and pasteurized milk, swabs of the inner surface of equipment (reception tank, pre-pasteurization tank, post-pasteurizationtank, package machine), walls and handlers hands. Quantitative analysis was performed by enumeration of Staphylococcus spp., which were targeted 114 isolates of this microorganism for ADN extraction and reaction of amplification for REP-PCR using the primer RW3A. Were observed package machine average counts of Staphylococcus spp. between plants of 5.18 CFU/mL for raw goat milk. The previous points of surface to pasteurization showed average counts of 0.65 and 1.55 log CFU/cm2 for reception tank and pre-pasteurization tank, respectively. For the points of surface after to the pasteurization, was observed counts of 0.94 and 1.65 log CFU/cm2 for lung tank and the package machine, respectively. Handlers hands showed average count of Staphylococcus spp. between plants of 0.88 log.CFU/hand. Still, wall surfaces showed an average count of 1.08 log CFU/cm2. For pasteurized milk, average count of Staphylococcus spp between 2.85 log CFU/mL was observed plants. In molecular analysis were observed indistinguishable genotypic profiles, as well as, genotypic profiles with high similarity of isolates of Staphylococcus spp. From pasteurized milk showed a genotypic profile similar to isolates of equipments and of handlers hand in the investigated plants, which, from individualized analysis in each plant, was allowed the identification of possible ways of milk contamination during your processing, which reinforced the quantitative analysis previously performed. The high contamination by Staphylococcus spp., and the close genotype relationship between the isolates of this microorganism in milk samples, equipments and handlers hands, reveals the presence of residual contamination and in plants of Cariri in state Paraiba, making it necessary to review in its Good Manufacturing Practices.